Immunostimulatory effect of ikan peda (fermented Rastrelliger sp.) water extract on IgM production by HB4C5 cells - Anindita, Michaela Maria Kanya; Putra, Agus Budiawan Naro; Sugahara, Takuya (Indonesian Journal of Life Sciences, 2019)
Ikan peda is one of Indonesia’s traditional fermented food products. It uses mackerel fish (Rastrelliger sp.), also known as ikan kembung in Indonesia, as its main ingredient. It is made through fermentation by adding high concentration of salt in order to extend the shelf-life and bring out the desired flavor of the fish. Although fermented foods are known to be beneficial towards health, fewer studies have been reported regarding the actual health promoting potential of Indonesian fermented foods, especially ikan peda. Thus, the immunostimulatory effects of ikan peda extract were examined. Water-extract of ikan peda was tested to human-human hybridoma HB4C5 cells. It was found that ikan peda extract stimulates the production of IgM by HB4C5 cells according to ELISA results. Data from real-time RT-PCR result showed that ikan peda extract has the ability to increase IgM gene expression by 3-fold at the highest concentration treatment. Results from the heat and enzyme treatments showed that the active substance contained in the ikan peda extract was expected to be a heat-stable protein. Although, the active substance and the mechanism is yet to be determined, and can be considered for future experiments. Our findings suggest that consumption of ikan peda would contribute to the promotion of health.